A Day in the Life of a Chisholm Trail Drover - Jim Hoy (Symphony in the Flint Hills, 2017)
Introduction: Before the Civil War, most Texas cattle were driven in small herds to markets by their owners, but in the boom following that war, entrepreneurs bought steers by the thousands to supply the demand for beef back East. A typical trail herd in this post-war era numbered between 2,000 and 3,000 head, and some cattlemen sent fifteen or more herds up the trail in a single season.
Keywords: Chisholm Trail; cattle drovers; drovers; life of a drover; night guard; herding; Kansas history; Texas history